Hubungan Antara Kadar Hemoglobin Ibu Hamil Dengan StatusGizi Anak Usia 0-6 Bulan Di Wilayah Kerja Puskesmas Sangkrah Kota Surakarta - Wulandari, Ratna Ayu (2016)
Background: Nutritional status is a condition of the body due to the consumption of food and use of nutrients. Reason infants have nutritional status is not good or stunting one of which is low hemoglobin levels mother during pregnancy. The research was conducted in the district of Kebumen known Puring mothers suffer from anemia in children is not good nutrition as much as 25%. Based on preliminary surveys in Puskesmas Sangkrah there are 216 children under five suffering stunting and 116 pregnant women with anemia. Purpose: To analyze the relationship between hemoglobin levels during pregnancy with the nutritional status of children aged 0-6 months infants at Puskesmas Sangkrah Surakarta. Methods: The study design was observational analytic study with case control approach. The samples are samples taken from the mother Hemoglobin levels of medical records third trimester of pregnancy and the nutritional status of a sample PB/U of children aged 0-6 months are taken when research in posyandu Puskesmas Sangkrah with purposive sampling technique of sampling. A large sample of 56 respondents. Results: Based on the Chi-square test and then it continues with fisher exact test, the variable hemoglobin levels of pregnant women with the nutritional status of children aged 0-6 months, with the result p = 0.401. Conclusions: There is no significant association between hemoglobin levels during pregnancy with the nutritional status of 0-6 months infants in Puskesmas Sangkrah Surakarta.